Google Drive to enhance the writing of argumentative texts - Santisteban Huima, Milagros Yacqueline (2023)
The writing of the argumentative texts is one of the difficulties that has been evidenced in the students. Therefore, this study was carried out with the objective of designing a didactic proposal integrating the Google Drive platform to enhance argumentative writing in secondary school students. The non-experimental design of a cross-sectional or cross-sectional nature was used; The sample included 30 students who were selected through non-probabilistic convenience sampling. The technique was observation and the instrument a checklist in which it was obtained as results that 62.5% are located in the not achieved level, while 31.25% are in the insufficient level and only 6.25% are in a sufficient level. In short, this research has a significant impact, since it promotes the development of argumentative skills using the functions of Google Drive, achieving a significant improvement in student learning.